Conservation through entertainment: Analyzing digital reception of wildlife messaging in popular Indonesian cinema - Nadhira Adesta Ramadhanti (Environment Conflict, 2025)
Background: Wildlife conservation is rarely portrayed in Indonesian cinema. Petualangan Sherina 2 (2023) brings attention to orangutan conservation and critiques the exploitation of wild animals by influencers. Despite ongoing online discourse and legal protections, public awareness remains low. This study explores how the film represents these issues through anthropocentric and biocentric perspectives. Methods: Using qualitative content analysis, key scenes, characters, and songs are examined to identify ecological values. Audience perception is assessed through sentiment data from Google Trends and social media posts on X (formerly Twitter). Findings: The film presents strong anthropocentric and biocentric messages. However, public interest peaked at the film’s release and quickly declined. Online responses focused more on nostalgia and entertainment than environmental themes. Conclusion: Petualangan Sherina 2 delivers a strong conservation message by blending entertainment and education. However, audience engagement remains limited, highlighting the need for ongoing media efforts. Nostalgia and cultural storytelling enhance the film's impact on biodiversity awareness. Novelty/Originality of this article: This study uniquely combines film analysis with digital sentiment tracking to evaluate environmental messaging in Indonesian popular cinema.